Sidonio Apollinare, Epitalamio per Ruricio e Iberia - Filosini, Stefania (Brepols, 2014)
About the mid-Fifties of 5th century AD, the Gallo-Roman aristocrat and gifted poet Sidonius Apollinaris composed an epithalamium to celebrate the marriage of his noble friends Ruricius and Hiberia. Sidonius did not know that in less than two decades he would become the bishop of Clermont-Ferrand, nor could Ruricius imagine that he would die the bishop of Limoges. Clinging to their profane models mostly represented by the epithalamia written by Statius and Claudian, the poem (carm. 11) and its preface (carm. 10) depict a world where the overwhelming presence of myth helps to keep reality aside and the skilled devices of a sophisticated poetry try to revive the formal perfection of Roman classics and their values. This volume provides a general introduction, a critical text with Italian translation, a punctual commentary (in fact the first one) to the epithalamium and its preface, and a summary in English; it shows the original contribution of Sidonius to the literary tradition of late Latin Epithalamia; it illustrates the techniques of the poet; it deals with the many exegetic problems presented by both poems and it proposes new solutions for some of them.